Alveolar proteinosis lung lavage using partial cardiopulmonary bypass. Issue 7 (July 1981) - Freedman, A P; Pelias, A; Johnston, R F; Goel, I P; Hakki, H I; Oslick, T; Shinnick, J P
Abstract : An adult case of pulmonary alveolar proteinosis presented with an arterial oxygen tension of 27 mmHg (3.6 kPa) while breathing air. Dangerous hypoxaemia during lung lavage was avoided by using partial cardiopulmonary bypass.